A Simple Method to Design and Analyze Dynamic Vibration Absorber of Pipeline Structure Using Dimensional Analysis - Mehrdad Shemshadi; Mahdi Karimi; Farzad Veysi (Shock and Vibration)
Vibrations due to mechanical excitation and internal and external fluid flow can cause fatigue in pipelines and leaks in fittings. A beam-based dynamic vibration absorber (beam DVA) is a device comprising an L-shaped beam with a concentrated mass at its free end that can be used to absorb and dissipate vibrations in the pipeline. In this paper, a mathematical equation is extracted to design the beam DVA using the dimensional analysis (DA) method and data recorded from 120 experimental tests. In the experimental studies, the pipes are fabricated in 1-inch, 2-inch, and 3-inch sizes. Each pipe is subjected to harmonic excitation at different frequencies, and the amplitude of vibration of the pipe is evaluated by changes in the geometric characteristics of beam DVA and concentrated mass. The proposed methodology is validated using the finite element method and simulation in the SIMULINK/MATLAB. The results showed that, out of the nine effective dimensionless parameters identified in pipe vibration control, mass ratio and stiffness ratio have the highest and lowest impacts on pipe vibration absorption, respectively.